2014
DOI: 10.1111/hex.12319
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to shared decisions in the most serious of cancers: a qualitative study of patients with pancreatic cancer treated in the UK

Abstract: Background Less than 20% of patients with pancreatic cancer present with localized, potentially curable tumours. Even when potentially curative surgery is possible, mortality is high. Only 20-25% of patients who have had resected ductal adenocarcinoma of the pancreatic head survive 5 years. Other treatments include chemotherapy, radiotherapy and palliative care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 30 publications
(27 reference statements)
1
29
0
1
Order By: Relevance
“…Other research shows that presenting the decision as a fact and not mentioning alternative options are common behaviours [31,32]. An alternative option, or even 'doing nothing', may come only into view only if patients are not eligible for a certain treatment [33]. We showed in a study on adjuvant cancer treatment that in only 3% of consultations it was stated that a (preference-sensitive) decision needed to be made.…”
Section: Are the Four Sdm Steps Implemented In Clinical Practice?mentioning
confidence: 90%
“…Other research shows that presenting the decision as a fact and not mentioning alternative options are common behaviours [31,32]. An alternative option, or even 'doing nothing', may come only into view only if patients are not eligible for a certain treatment [33]. We showed in a study on adjuvant cancer treatment that in only 3% of consultations it was stated that a (preference-sensitive) decision needed to be made.…”
Section: Are the Four Sdm Steps Implemented In Clinical Practice?mentioning
confidence: 90%
“…Another reason for the divergence in perception might be due to patients reporting that there was no choice to be made, as reported elsewhere [18,19]. Ziebland et al and Charles et al found patients commenting that there was no decision to be made if there was only one treatment option [18,19].…”
Section: Discussionmentioning
confidence: 98%
“…, Ziebland et al . ). The research team had extensive discussions about the rationale and meaning of the interview items to ensure comparable data were collected.…”
Section: Methodsmentioning
confidence: 97%